Implementation of Paragogy Praxis to Develop Students’ Holistic Capacities in Online Learning - Tiyas Abror Huda; Een Yayah Haenilah; Asih Budi Kurniawati (Institute of Advanced Knowledge and Science, 2026)
This study is motivated by the challenges of online learning in fostering students’ holistic competencies, particularly in social and moral dimensions that are often underemphasized. It aims to describe the implementation of paragogy praxis in developing students’ holistic competencies in an online learning environment. A quantitative approach with a descriptive design was employed, involving 869 second-semester students from the Faculty of Teacher Training and Education at Universitas Lampung. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, and were analyzed using descriptive statistics. The findings reveal that students’ holistic competencies, encompassing intellectual, social, and moral aspects, are categorized as very high. This is reflected in strong levels of empathy, collaboration, and self-regulation, which indicate ethical, reflective, and responsible interactions among students. In addition, female students tend to demonstrate slightly higher holistic competencies than male students, although the difference is not statistically significant. Based on the study program, students from the Primary School Teacher Education (PGSD) program show the highest achievement in holistic competencies. These findings suggest that the implementation of paragogy praxis in online learning is effective in supporting the development of students’ holistic competencies. This approach not only emphasizes cognitive aspects but also promotes social interaction, collaboration, and the internalization of moral values through technology-mediated collaborative learning. Therefore, paragogy praxis can be considered a relevant alternative pedagogical approach in addressing educational challenges in the digital era.